Modelling the shelf circulation off eastern Tasmania. (1st November 2016) - Oliver, Eric C.J.; Herzfeld, Mike; Holbrook, Neil J.
Abstract: The marine waters across Tasmanian's eastern continental shelf are biologically productive and home to economically important fisheries and aquaculture industries. However, the marine climate there is poorly understood. We use a high-resolution (∼2 km in the horizontal), three-dimensional ocean model for eastern Tasmania (ETAS) to examine the simulated mean state and seasonal cycle of temperature, salinity and three-dimensional flow field, and the evaluation of daily model outputs against in situ and remote observations for the 1993–2014 period. We also use the model to examine the roles of river input and tidal forcing. The model is evaluated against remotely-sensed sea surface temperature and in-situ observations of sea level and subsurface temperature, salinity, and currents. The mean state demonstrates the influence of two well-known boundary currents (the East Australian Current, EAC, and the Zeehan Current, ZC) as well as the effects of local freshwater input from river runoff. The EAC is dominant in summer and the ZC in winter; the influence of the EAC also increases northwards and in the offshore direction. In addition, the model indicates the presence of a semi-permanent subsurface (50–100 m depth) northward flow trapped near the coast. Cool freshwater runoff from the Derwent and Huon Rivers directly impacts the temperature and salinity in their estuaries but has little influence further across the shelf. Tidal forcing impacts the mean state through tide-river interactions which flush Frederick Henry Bay and Norfolk Bay with freshwater. Tidal forcing also impacts the variability of temperature all along the coastline, most likely due to changes in the turbulent mixing near to the coast. The ETAS model output data are available as a high-resolution representation of the mean state, seasonal variations, and interannual variability of Tasmania's eastern continental shelf marine climate. Abstract : Highlights: We model the mean and seasonal cycle of circulation off eastern Tasmania. Both the Zeehan Current and the East Australian Current are present in the mean. The Zeehan Current is dominant in Austral winter. The East Australian Current is dominant in Austral summer. Rivers cool and freshen estuaries while tides have complex interactions with rivers.